Pr3+ Visible to Ultraviolet Upconversion for Antimicrobial Applications - Miroslav D. Dramićanin; Mikhail G. Brik; Željka Antić; Radu Bănică; Cristina Mosoarca; Tatjana Dramićanin; Zoran Ristić; George Daniel Dima; Tom Förster; Markus Suta (Nanomaterials)
This paper addresses the upconversion of blue light to ultraviolet-C (UVC) with Pr3+-activated materials for antibacterial applications of UVC. It discusses the processes through which UV radiation provides biocidal effects on microorganisms, along with the most popular UVC sources employed in these processes. We describe the electronic and optical properties of the Pr3+ ion, emphasizing the conditions the host material must meet to obtain broad and intense emission in the UVC from parity-allowed transitions from the 4f5d levels and provide a list of materials that fulfill these conditions. This paper also delineates lanthanide-based upconversion, focusing on Pr3+ blue to UVC upconversion via the 3P0 and 1D2 intermediate states, and suggests routes for improving the quantum efficiency of the process. We review literature related to the use of upconversion materials in antimicrobial photodynamic treatments and for the blue to UVC upconversion germicidal effects. Further, we propose the spectral overlap between the UVC emission of Pr3+ materials and the germicidal effectiveness curve as a criterion for assessing the potential of these materials in antimicrobial applications. Finally, this paper briefly assesses the toxicity of materials commonly used in the preparation of upconversion materials.